2002
DOI: 10.1046/j.1440-1843.2002.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, laboratory findings and microbiologic characterization of bronchiectasis in Thai patients

Abstract: We report the characteristics of bronchiectasis in Thai patients. The most common identifiable aetiology was tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 14 publications
(27 reference statements)
3
48
0
Order By: Relevance
“…Although decreasing, the prevalence of TB in Korea was very high up to over 1,000 active cases of 100,000 subjects in the nationwide survey in 1995 (Hong et al 1998). In a study on the Thai population, TB was identified as the most common etiology for bronchiectasis (32% of patients) (Palwatwichai et al 2002). The association of TB with bronchiectasis could explain the very high prevalence of bronchiectasis in our population.…”
Section: Respiratory Symptoms % (N)mentioning
confidence: 65%
“…Although decreasing, the prevalence of TB in Korea was very high up to over 1,000 active cases of 100,000 subjects in the nationwide survey in 1995 (Hong et al 1998). In a study on the Thai population, TB was identified as the most common etiology for bronchiectasis (32% of patients) (Palwatwichai et al 2002). The association of TB with bronchiectasis could explain the very high prevalence of bronchiectasis in our population.…”
Section: Respiratory Symptoms % (N)mentioning
confidence: 65%
“…The bronchiolar disorders which most frequently have features of bronchiectasis on HRCT scanning are constrictive bronchiolitis (obliterative bronchiolitis) and diffuse panbronchiolitis, the latter largely confined to patients of Far Eastern ethnic origin which is reflected in a higher incidence of the disorder in case series from that geographical area145 compared with the UK 22…”
Section: Summary Of Recommendationsmentioning
confidence: 99%
“…The cough is productive of sputum daily in 75–100%, on an intermittent basis in 12–20% and non-productive in 5–8% 46 53 145 245. Assessment of volume may be by patient and clinician estimate and, in the literature, the convention is to compare the volume of sputum produced in 24 h with easily recognisable units such as a teaspoon (5 ml), dessert spoon (10 ml), tablespoon (15 ml), egg cup (30 ml) or tea cup (200 ml) 223 239.…”
Section: Section 3: Clinical Assessment and Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were three DPB cases published each from India [26][27][28] and Turkey, [29][30][31] and two case studies each from Belgium, 32,33 Brazil, 34,35 Germany, 36,37 and Thailand. 38,39 One case report each was reported from Canada, 40 Ireland, 41 Malaysia, 42 Netherlands, 43 New Zealand, 44 Norway, 45 Portugal, 46 Singapore, 47 Spain, 48 and the UK. 4 It is interesting to note that a majority (50%, n=24) of DPB studies were from four developed countries.…”
mentioning
confidence: 99%